MARCHF8-mediated ubiquitination via TGFBI regulates NF-κB dependent inflammatory responses and ECM degradation in intervertebral disc degeneration. - Xingpeng Zhang; Guang Li; Fang Tan; Tao Yu; Chengping Xu; Kai Li; Feng Zhang; Meiyan Zhang; Jian Wang (PLoS ONE)
Aim To explore the role of the hub gene Transforming Growth Factor Beta Induced (TGFBI) in Intervertebral disc degeneration (IDD) pathogenesis and its regulatory relationship with Membrane Associated Ring-CH-Type Finger 8 (MARCHF8). Background IDD is a prevalent musculoskeletal disorder leading to spinal pathology. Despite its ubiquity and impact, effective therapeutic strategies remain to be explored. Objective Identify key modules associated with IDD and understand the impact of TGFBI on nucleus pulposus (NP) cell behavior, extracellular matrix (ECM)-related proteins, and the Nuclear Factor kappa-light-chain-enhancer of Activated B cells (NF-κB) signaling pathway. Methods The GSE146904 dataset underwent Weighted Gene Co-Expression Network Analysis (WGCNA) for key module identification and Differentially Expressed Genes (DEGs) screening. Intersection analysis, network analysis, and co-expression identified TGFBI as a hub gene. In vitro experiments delved into the interplay between TGFBI and MARCHF8 and their effects on NP cells. Results WGCNA linked the MEturquoise module with IDD samples, revealing 145 shared genes among DEGs. In vitro findings indicated that MARCHF8 determines TGFBI expression. TGFBI boosts apoptosis and ECM breakdown in Lipopolysaccharide-stimulated (LPS-stimulated) NP cells. Altering TGFBI levels modulated these effects and the NF-κB signaling pathway, influencing inflammatory cytokine concentrations. Moreover, MARCHF8 ubiquitination controlled TGFBI expression. Conclusion TGFBI, modulated by MARCHF8, significantly influences IDD progression by affecting NP cell apoptosis, ECM degradation, and inflammation through the NF-κB signaling pathway.